Cochrane Database of Systematic Reviews 2012
DOI: 10.1002/14651858.cd010033
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic third ventriculostomy (ETV) for idiopathic normal pressure hydrocephalus (iNPH)

Abstract: Endoscopic third ventriculostomy (ETV) for idiopathic normal pressure hydrocephalus (iNPH).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…While surgeons have attempted ETV for elderly patients with iNPH, 14 the published results have not convincingly demonstrated efficacy. 24,29 The clinical triad of findings of iNPH (dementia, gait disturbance, and incontinence) are well known, but the pathophysiology is not understood. There is speculation that symptoms are related to stretching of the subcortical motor and dopaminergic pathways and the frontostriatal pathways.…”
Section: Discussionmentioning
confidence: 99%
“…While surgeons have attempted ETV for elderly patients with iNPH, 14 the published results have not convincingly demonstrated efficacy. 24,29 The clinical triad of findings of iNPH (dementia, gait disturbance, and incontinence) are well known, but the pathophysiology is not understood. There is speculation that symptoms are related to stretching of the subcortical motor and dopaminergic pathways and the frontostriatal pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an important part of the iNPH investigation is to identify and treat any treatable comorbidities and discuss their potential influence on surgical outcome with the patient and family. If there is any doubt as to 25,26 As of 2016, no medical treatments are effective in iNPH, and, specifically, no evidence supports the use of acetazolamide, 27 although this medication is occasionally prescribed and has been evaluated in a small pilot study. 28…”
Section: Role Of Comorbiditiesmentioning
confidence: 99%
“…A 2015 Cochrane review reported that the only randomized controlled trial on endoscopic third ventriculostomy versus shunting to meet its criteria for inclusion was unable to determine the effectiveness of the technique due to the use of a nonstandard comparator arm (VP shunting using nonprogrammable valves). 78 As compared with endoscopic third ventriculostomy, results for VP shunting still appear superior. 64,66 Diffusion tensor imaging-A New Direction?…”
Section: Unifying Theoriesmentioning
confidence: 99%